ANALISIS PENINGKATAN PENDAPATAN USAHA PENGRAJIN ROTAN DITINJAU DARI EKONOMI SYARIAH DI DESA PIANTUS KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Bella, Icha; Iva Ashari Ananda; Radimin (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
Ratten crafts are one of the cultures in Piantus Village, Sejangkung District which is now being developed and has become a source of income for the local community. However, in its development to increase the income of rattan craftsmen, there are still many obstacles. For this reason, this study will discuss how rattan craftsmen try to increase their income. This study aims to determine the increase in the income of Rattan craftsmen in Piantus Village, Sejangkung District, Sambas Regency. In addition, to determine the supporting and inhibiting factors for increasing the income of Rattan Craftsmen in Piantus Village, Sejangkung District, Sambas Regency.This study is included in qualitative research, which emphasizes quality or the most important thing of a good or service. This study will conduct research on sources, namely rattan craftsmen, using three data collection techniques, namely Observation, Documentation and Interviews.The results of this study indicate that the increase in income from rattan craft businesses in Piantus Village, Sejangkung District, is known to have several efforts to increase their income, including the following: First, they increase business capital, either from loans or cooperatives. Second, efforts to increase income carried out by rattan craftsmen in Piantus Village are by providing motivation and increasing business development capabilities for both the craftsman owners and their employees. Third, there are several rojan craftsmen in Piantus Village who have participated in economic business skills training as an effort to increase their income. Meanwhile, supporting factors for rattan craftsmen are strategic location, raw materials are easy to obtain, many workers, easy transportation facilities and marketing can be done easily. In addition to supporting factors, there are also inhibiting factors, namely internal and external factors.